Diseño e implementación de un sistema generador de energía eléctrica mediante el uso de dispositivos piezoeléctricos implementados en una máquina elíptica en el gimnasio “zeus” ubicado en la ciudad de machachi – cantón mejía - Guacapiña Simba, Brayan Ivan (2019)
With the design and implementation of an electric power generating system through the use of piezoelectric devices implemented in an elliptical machine in the “Zeus” gym located in the city of Machachi - Mejia Canton, it is sought to generate a new technological proposal to provide electricity consumption of mobile devices, which is why this proposal is mitigated by reducing the negative ecological impact generated by current sources of electricity generation since national energy expenditure is increasing. The scientific method, inductive-deductive, quantitative, and measurement and calculation techniques are the essential mainstay for the development of the technological approach since with these the effective design for the implementation can be determined, focused on the collection and storage of harvesting energy, the behavior of flexible piezoelectric devices at the time of deformation, the configuration of piezoelectric connection, the amount of piezoelectric necessary and calculations for the storage system and delivery of electrical energy necessary for the power consumption of mobile phone electricity generating a quantity of 24W per elliptical machine through 7 piezoelectric banks connected in parallel which each one are made up of 5 flexible devices giving a quantity of 35 piezoelectric with the daily use of the elliptical machine in the gym, this process guarantees the efficient operation of this generation system which generates a great impact for society and the environment, encouraging people to exercise and also help the planet.